2002
DOI: 10.1038/sj.onc.1205750
|View full text |Cite
|
Sign up to set email alerts
|

pRb2/p130 promotes radiation-induced cell death in the glioblastoma cell line HJC12 by p73 upregulation and Bcl-2 downregulation

Abstract: This study shows that in the glioblastoma hamster cell line HJC12 the retinoblastoma family member pRb2/ p130 enhances g-radiation-induced cell death. In HJC12 cells the tetracycline-regulated expression of pRb2/p130 increased the percentage of g-radiation-induced apoptotic cells from 27 to 47%. pRb2/p130 overexpression was associated with the downregulation of the anti-apoptotic factor Bcl-2 and the upregulation of the steady-state protein levels of the pro-apoptotic transcription factor p73. In particular, R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…The antiapoptotic effect of pRb2/p130 is consistent with previous studies proving a protective role of the pRb/p105 member of the Rb family in apoptosis induced by CPT (12). Nevertheless, the effects of pRb2/p130 may vary under different conditions, as seen in a previous study (14), in which a proapoptotic role of pRb2/p130 in ␥-radiation-induced cell death is demonstrated. The decrease in pRb2/p130 expression detected in many tumors as well as in ovarian cancer is likely to cause a greater effect of CPT and DOX on the tumor and a lesser effect on the normal tissue, consequently leading to milder side effects in patients.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The antiapoptotic effect of pRb2/p130 is consistent with previous studies proving a protective role of the pRb/p105 member of the Rb family in apoptosis induced by CPT (12). Nevertheless, the effects of pRb2/p130 may vary under different conditions, as seen in a previous study (14), in which a proapoptotic role of pRb2/p130 in ␥-radiation-induced cell death is demonstrated. The decrease in pRb2/p130 expression detected in many tumors as well as in ovarian cancer is likely to cause a greater effect of CPT and DOX on the tumor and a lesser effect on the normal tissue, consequently leading to milder side effects in patients.…”
Section: Discussionsupporting
confidence: 79%
“…A study conducted in mice supports an antiapoptotic role of p107 (13). Our recent findings suggest a role of pRb2/p130 in glioblastoma ␥-radiation-induced apoptosis (14), whereas restoring the function of pRb/p105 in a pRb/ p105-null osteosarcoma cell line inhibits radiation-induced apoptosis (15), thus indicating different roles of the Rb family members in cell apoptosis. The present study was carried out to assess the role of pRb2/p130 in apoptosis driven by camptothecin (CPT), doxorubicin (DOX), and taxol (TX) in human ovarian carcinoma CAOV-3 cells, which exhibit a lack of wildtype p53, the most common genetic alteration in human cancer.…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been reported that ectopic expression of pRb2/p130 is associated with downregulation of the antiapoptotic factor bcl-2 and upregulation of p73 (Pucci et al, 2002), suggesting that it might regulate p73 expression. We studied the in vivo occupancy of p73 promoter by pRb2/p130 and our results suggest a direct role of this protein in regulating p73 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Tumors concomitantly lacking pRb/p105 and p53, such as osteosarcoma cells, are, however, still able to undergo apoptosis, thus suggesting a possible role in this process of another pRB family protein to regulate the p53-dependent and -independent apoptosis. Few data are available on the role of the two retinoblastoma-related family members, pRb2/p130 and p107, in the apoptotic response even if a possible role of pRb2/p130 in regulating the expression of the antiapoptotic bcl-2 and of the proapoptotic p73 proteins has recently been indicated (Pucci et al, 2002). Moreover, an inverse correlation between pRb2/p130 expression level and apoptotic index in retinoblastoma tumor has been reported, suggesting a possible involvement of pRb2/p130 in the apoptotic response (Bellan et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Future experiments should investigate the physiological contexts in which this novel activity is most significant, including mouse models of cancer. One report in glioblastoma cells suggests that the RB family member p130 can potentiate the cell death induced by DNA damage in glioblastoma cells (Pucci et al 2002). It would be interesting to know whether p130 and the other RB family member, p107, both of which share functional and structural similarities with RB, also share its capacity to interact with Bax and regulate apoptotic cell death directly.…”
Section: Similarities and Differences Between Rb And P53mentioning
confidence: 99%